Root-Knot Nematode Resistance in Peanut - Jim Rich; Barry Tillman (EDIS)
ENY-057, a 4-page illustrated fact sheet by Jim Rich and Barry Tillman, describes root-knot disease, its symptoms, and progress of the development of cultivars resistant to root-knot nematode, grower options, and promising near-term research. Includes references. Published by the UF Department of Entomology and Nematology, November 2007.